2018
DOI: 10.1021/acs.energyfuels.7b04058
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Effects of Heavy Feeds on the Deactivation of a Commercial Atmospheric Residue Desulfurization Catalyst System

Abstract: The effect of three atmospheric residual oils on the deactivation of a commercial atmospheric residue desulfurization (ARDS) catalyst system was assessed using a commercial catalyst system consisting of five catalysts loaded inside a two-reactor pilot plant. The hydrodemetalation (HDM) and hydrodesulfurization (HDS) reactions of the three residues over the catalyst system were studied. A deactivation model considering metals and carbon deposition was used to fit the life test data. Experimental and simulated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(95 reference statements)
1
5
0
Order By: Relevance
“…Also the degradation of pore structure parameters observed for CAT-1 and CAT-2 justifies the activity loss observed for both catalyst samples with ��� 0 =059 mm, which is found to be 20 and 11% respectively [14]. The analysis of the porous structure of spent CAT-1 and CAT-2 showed that the most probable diameters of pores had dropped to 45 and 51 ( Å) for dp (1) and to 75 and 82( Å) for dp (2) for both samples respectively. The micro-pores with diameters less than 20 Angstrom (Å) were seriously infected and isolated.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…Also the degradation of pore structure parameters observed for CAT-1 and CAT-2 justifies the activity loss observed for both catalyst samples with ��� 0 =059 mm, which is found to be 20 and 11% respectively [14]. The analysis of the porous structure of spent CAT-1 and CAT-2 showed that the most probable diameters of pores had dropped to 45 and 51 ( Å) for dp (1) and to 75 and 82( Å) for dp (2) for both samples respectively. The micro-pores with diameters less than 20 Angstrom (Å) were seriously infected and isolated.…”
Section: Resultssupporting
confidence: 55%
“…6. Vp (1) 0.37 89.5 0.37 95 Vp (2) 031 95.3 0.32 93 dp (1), ( Å) 57 68.7 65 74 dp (2) , ( Å) 115 93.5 122 95.3 Samples with larger particle having ��� 1 = 0.326 mm showed the results given in Table 8. The spent catalyst samples showed a higher loss in their pore structure parameters [ Tables 8,9].…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations